An 8 m/9.6 Gbps Underwater Wireless Optical Communication System - Hai-Han Lu; Chung-Yi Li; Hung-Hsien Lin; Wen-Shing Tsai; Chien-An Chu; Bo-Rui Chen; Chang-Jen Wu (IEEE Photonics Journal, 2016)
An 8 m/9.6 Gbps underwater wireless optical communication (UWOC) system based on a two-stage injection-locked 405 nm blue light laser diode (LD) transmitter with a 16-quadrature amplitude modulation (QAM)-orthogonal frequency-division multiplexing (OFDM) modulating signal is proposed and experimentally demonstrated. To the best of our knowledge, it is the first one that employs a two-stage injection-locked technique to improve the transmission performance of UWOC systems. With the assistance of an equalizer at the receiver site, acceptable bit error rate (BER) performance and a constellation map are obtained over an 8-m underwater link. Such a two-stage injection-locked 405 nm blue light LD transmitter-based UWOC system is shown to be a promising alternative, presenting its feasibility for long-range and high-speed underwater links.